2020
DOI: 10.1007/s42765-020-00037-9
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photocatalytic Performance of Surface-Modified TiO2 Nanofibers with Rhodizonic Acid

Abstract: The improvement of the photocatalytic performance of TiO 2 nanofibers (NFs), prepared by electrospinning, is achieved by surface modification with the rhodizonic acid (RhA). The condensation reaction between hydroxyl groups from TiO 2 NFs and RhA is accompanied by the red-shift of optical absorption due to interfacial charge transfer (ICT) complex formation. Crystal structure, morphology, and optical properties of unmodified and surface-modified TiO 2 NFs were analyzed. The photocatalytic performance of prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(29 citation statements)
references
References 13 publications
1
28
0
Order By: Relevance
“…Advanced oxidation processes (AOPs) have been widely practiced to eliminate organic pollutants [6]. Particularly, the photo Fenton oxidation process has been proved its high-efficiency and environmentally friendliness in the degradation of organic pollutants in wastewater [7][8][9][10][11]. Nevertheless, homogenous Fenton oxidation reactions encountered limitations such as the generation of ferric hydroxide sludge, the use of strong acid and the poor reusability of the catalyst [12].…”
Section: Introductionmentioning
confidence: 99%
“…Advanced oxidation processes (AOPs) have been widely practiced to eliminate organic pollutants [6]. Particularly, the photo Fenton oxidation process has been proved its high-efficiency and environmentally friendliness in the degradation of organic pollutants in wastewater [7][8][9][10][11]. Nevertheless, homogenous Fenton oxidation reactions encountered limitations such as the generation of ferric hydroxide sludge, the use of strong acid and the poor reusability of the catalyst [12].…”
Section: Introductionmentioning
confidence: 99%
“…6 Sun also reported that surface-modified TiO 2 nanofibers with rhodizonic acid showed enhanced photocatalytic performance. 7 As for ZrO 2 semiconductor, its wide band gap prohibits its use as an efficient solar photocatalyst. 8 While many successful attempts have been reported to improve the photocatalytic activity of ZrO 2 by building structures of different type, [9][10][11] it remains a challenge to modify the surface structure of ZrO 2 superstructures.…”
Section: Introductionmentioning
confidence: 99%
“…Among monoclinic ZrO 2 (M-ZrO 2 ) relaxed facets, the highest energy surface is (010) facets, 8 Chen et al evidenced that the simultaneous exposure of the (100) and (010) facets over the M-ZrO 2 nanorods could promote the formation of superoxide O 2− species, 4 that will be of great benefit to the adsorption and oxidative degradation of organic contaminants in waste water. Nevertheless, M-ZrO 2 nanoparticles are usually dominated by low-index (110), (011), ( 111), (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11), and (001) facets, 8,13,14 while the metastable (010) facets usually conceal rapidly during the synthesis process. In particular, to our knowledge, hollow microspherical assemblies by M-ZrO 2 nanosheets with a high percentage of exposed (010) facets have not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, membranes have been modified by using titanium dioxide (TiO 2 ) nanotubes; this modification usually result in change of shape and size of nanomaterials [20,21]. TiO 2 nanotubes have also shown several benefits such as higher surface area, high hydrophilic properties, improved photocatalytic activity, increased robustness and excellent mechanical stability [21,22]. X. Cao et al studied the effect of titania nanoparticles on the PVDF membrane.…”
Section: Introductionmentioning
confidence: 99%